End-to-end jejunal anastomosis with bovine pericardium xenograft in equines - Aguilar G., Ceesar N. (2018)
The feasibility of untreated bovine pericardium xenograft as biomaterial for the lining of the small intestine anastomosis in horses to avoid dehiscences, leakage, fistulas and formation of adhesions in the postoperative period was investigated. Seven horses were submitted to end-to-end jejunal anastomosis coated with untreated bovine pericardial xenograft and a control group of seven horses submitted to end-to-end jejunal anastomosis only. Postoperative pain, cellular components and organoleptic characteristics of the peritoneal fluid were evaluated. It was found that the bovine pericardium xenograft coating does not generate significant differences in the quantification of pain (postoperative colic) nor in the total nucleated cell count of the peritoneal fluid nor does it influence the alterations of the color, turbidity and smell of the peritoneal fluid, demonstrating that untreated bovine pericardial xenograft as a covariant of the jejunal anastomosis does not influence the functions of the alimentary system from the point of view of the postoperative clinical examination. It is concluded that untreated bovine pericardium xenograft is viable and effective because it reinforces the cicatricial remodeling process, avoiding possible anastomotic leakage and peritonitis